Teaching Ethnic-Specific Coursework: Practical Suggestions for Promoting Diversity, Equity, and Inclusion Within the Classroom. (October 2022) - Arellanes, Jordan A.; Hendricks, Michael
Background: Access to professors willing and trained to teach courses related to specific ethnic groups may be difficult for many universities to provide. This may partially explain why many psychology departments do not offer undergraduate courses that focus on the unique perspectives of specific ethnic groups. Objective: This study offers practical suggestions for instructors in promoting inclusivity within the classroom detailed though perceptions of students. Method: Focus groups were conducted with 27 students within four ethnic-specific courses. Focus groups were divided into comparison groups: 1) those that ethnically matched the course material and 2) those that did not. Results: Ethnic-specific coursework provides space to address systemic issues. Implications from ethnic matching, inclusion efforts within the classroom, and building a class community are discussed. Conclusions: Diversity, equity, and inclusion efforts are supported when departments offer ethnic-specific courses. The trust and communication with students are improved by constructing effective course frameworks. Teaching Implications: We inform the development and implementation of ethnic-specific psychology courses by highlighting practical considerations for instructors of varying ethnic backgrounds. Instructors from varied backgrounds can effectively teach these courses but having applied experiences and research related to specific ethnic groups is essential in developing trust and communication with students.